Managerial Stress Management as an Asset in People Management Being a Marketing Strategy Element - Radnović, Branislav; Radnović, Vladana (Industrija, 2013)
Any service organization operating under turbulent market conditions must have a successful marketing strategy. A successful marketing strategy implies proper management of all elements within a marketing mix: service package, price, distribution channels, promotion, service process, service ambience and people. People, i.e. primarily the employed within an organization are one of the elements that must be appropriately considered when drawing up and implementing a marketing strategy. Proper personnel management must nowadays include good management of managerial stress. Adequate managerial stress management is preconditioned by successful identification of sources of managerial stress. The aim of this paper is to present the importance of proper and timely identification of sources of managerial stress. The paper demonstrates the carried out scientific research based on a method that is universal for all types of organizations, regardless of their type and activity, in order to precisely identify the sources of managerial stress and define its proper management, as an asset in people management, which is an element of marketing strategy. The research was conducted using a survey, sampling 100 employees in 13 organizations throughout Serbia. Survey results indicated that the most important sources of managerial stress are: participation in decision-making, selection process, earnings, and time and deadlines pressure. Therefore, recommendations are provided for directing identified sources of managerial stress towards successful management of people as an element of marketing strategy.